Lipids and sterol from Berberis vulgaris L. var. asperma - Ragasa, Consolacion Y. (Animo Repository, 2015)
Chemical investigation of the dichloromethane extract of the fruit of Berberis vulgaris L. var. asperma afforded mixtures of saturated carboxylic acid, (2Z)-3-(4-hydroxyphenyl)-2-propen-1-yl esters (1), fatty acid esters (2), fatty alcohols (3), triacyl glycerols (4), monoacyl glycerols (5), fatty acids (6); and β-sitosterol (7). The structures of 1and2 were elucidated by extensive 1D and 2D NMR spectroscopy, while those of 3-7 were identified by comparison of their NMR data with literature data.